2020
DOI: 10.15406/mojwh.2020.09.00266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D3, calcium and exercise in the management of osteoporosis

Abstract: Osteoporosis is a disease related to bone metabolism disorder. It is characterized by low bone mass and deterioration of the micro architecture, whose consequence is greater bone fragility and an increased risk of fractures. The purpose of this review is to summarize literature review regarding dietary calcium and vitamin d intake and exercise interventions for the treatment of osteoporosis in isolation. Recommendations as adequate amounts of total calcium, vitamin D and protein intake, regular exercise to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The combined supplementation of vitamin D and calcium showed a positively increased BMD 16 . Many studies revealed that regular calcium and vitamin D has the ability to prevent reduced bone density and thereby fracture 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined supplementation of vitamin D and calcium showed a positively increased BMD 16 . Many studies revealed that regular calcium and vitamin D has the ability to prevent reduced bone density and thereby fracture 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that osteopenia was more in not doing physical exercise for health professionals than doing exercise. One study done on female medical students in Pakistan showed that only one-fourth of participants did regular exercise, and three-fourths of female students did not do regular exercise, out of one-fourth of participants doing regular exercise nearly one-third had osteopenia 18,19 .…”
Section: Discussionmentioning
confidence: 99%